Escherichia coli Cytotoxic Necrotizing Factor and Pasteurella multocida Toxin Induce Focal Adhesion Kinase Autophosphorylation and Src Association - Thomas, Warren (American Society for Microbiology, 2001)
Cytotoxic necrotizing factor 1 and Pasteurella multocida toxin induced dose- and time-dependent increases in focal adhesion kinase (FAK) Tyr(397) phosphorylation in Swiss 3T3 cells. FAK autophosphorylation was sensitive to inhibitors of p160/ROCK and coincided with the formation of stable complexes between FAK and Src family members.